2021
DOI: 10.1111/jac.12496
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing revealed the molecular mechanism of response of pearl millet root to heat stress

Abstract: Temperature is an abiotic stressor often encountered in the life cycle of plants. High temperature can affect the growth and development of plants (Suraweera et al., 2020). According to a previous report (PICC 2014; http://www.ipcc.ch/), by the end of this century, the average temperature will increase by a maximum of approximately 4°C, and the temperature will increase by 0.2°C every ten years. Global warming will reduce the average output of millet and sorghum by 10%-20%(2.33-4.02 billion USD) and 5%-15% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Several investigations have been carried out to identify and characterize the candidate genes/proteins and small RNAs involved in the root's response to thermal stress. A root‐specific transcriptomic‐based differentially expressed genes analysis was conducted in 13‐day‐old seedlings of Pennisetum glaucum (pearl millet) exposed to short‐duration heat stress [40/35°C and control (26/21°C) for 7 h; root tissue harvested at 1, 3 and 7 h] (R. Sun et al, 2021). The analysis revealed that HSFs and the endoplasmic reticulum stress pathway were mainly affected after 1 h of heat stress (R. Sun et al, 2021).…”
Section: Physio‐morphological and Molecular Dynamics Associated With ...mentioning
confidence: 99%
“…Several investigations have been carried out to identify and characterize the candidate genes/proteins and small RNAs involved in the root's response to thermal stress. A root‐specific transcriptomic‐based differentially expressed genes analysis was conducted in 13‐day‐old seedlings of Pennisetum glaucum (pearl millet) exposed to short‐duration heat stress [40/35°C and control (26/21°C) for 7 h; root tissue harvested at 1, 3 and 7 h] (R. Sun et al, 2021). The analysis revealed that HSFs and the endoplasmic reticulum stress pathway were mainly affected after 1 h of heat stress (R. Sun et al, 2021).…”
Section: Physio‐morphological and Molecular Dynamics Associated With ...mentioning
confidence: 99%
“…The experimental conditions of the control group were set to 26 • C for 14 h under light and at 21 • C for 10 h in the dark. The conditions of the heat treatment group were 40 • C for 14 h under light and 10 h in the dark at 35 • C [6]. 50% Hoagland nutrition mix (1 mM MgSO 4 , 1 mM KH 2 PO 4 , 1 mM NH 4 NO 3 , 0.5 mM CaCl 2 , 0.1 mM FeNa-EDTA, 25 mM NaCl, 0.1 mM H 3 BO 3 , 0.1 mM Na 2 SiO 3 , 1.5 µM CuSO 4 , 50 µM KCl, 10 µM MnSO 4 , 0.075 µM Na 2 MoO 4 and 2 µM ZnSO 4 ) was used to provide nutrients throughout the cultivation stage and treatment period of the plant.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…The production of pearl millet (Pennisetum glaucum (L.) R. Br) is the sixth largest cereal crop, right after wheat, rice, corn, sorghum and barley production [6]. Its planting area reaches 31 million hectares, which provides food and income sources of 90 million people (ICRISAT; https://www.icrisat.org/, 21 July 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The former scenario would reflect the reduced thermal tolerance of P. macrosturtensis, which is also supported by the species differentially expressing a far lower number of genes in response to higher temperatures compared to P. nigroadumbratus. Similarly reduced numbers of differentially expressed genes have also been associated with lower thermal tolerances in other organisms such as fish (Narum & Campbell, 2015), lizards (Akashi et al, 2016), rotifers (Paraskevopoulou et al, 2020, red algae (W. Wang et al, 2018), and plants (Jin et al, 2020;Sun et al, 2021), though we note the inverse (or alternatively, no clear pattern) has been observed in a number of cases, potentially reflecting lower levels of stress as opposed to an inability to mount a HSR (DeBiasse & Kelly, 2016;Perez et al, 2021).…”
Section: The Subterranean Species Paroster Macrosturtensis Retains a Heat Shock Responsementioning
confidence: 99%